2019
DOI: 10.1371/journal.pone.0212835
|View full text |Cite
|
Sign up to set email alerts
|

A standardized methodical approach to characterize the influence of key parameters on the in vitro efficacy of extracorporeal photopheresis

Abstract: Extracorporeal photopheresis (ECP) is an autologous immunomodulatory cell therapy that consists of the ex vivo collection of mononuclear cells (MNCs), which are irradiated with UVA in the presence of the photosensitizing agent 8-methoxypsoralen (8-MOP) to induce cell apoptosis. This photoactivated cell preparation is then reinfused into the patient. While the clinical benefits of ECP are well-demonstrated, no study has yet characterized the influence of variations in the composition of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 42 publications
(49 reference statements)
1
15
0
2
Order By: Relevance
“…Similarly, Laulhé et al observed that 8-MOP adsorption was significantly higher in NaCl (79%) than in plasma (94%), resulting in the inhibition of lymphocyte proliferation and an increase in T-cell apoptosis. 21 Hence, plasma seems to be associated with lower bioavailability of 8-MOP even though adsorption is less pronounced. This could be caused by protein binding of 8-MOP in plasma.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Laulhé et al observed that 8-MOP adsorption was significantly higher in NaCl (79%) than in plasma (94%), resulting in the inhibition of lymphocyte proliferation and an increase in T-cell apoptosis. 21 Hence, plasma seems to be associated with lower bioavailability of 8-MOP even though adsorption is less pronounced. This could be caused by protein binding of 8-MOP in plasma.…”
Section: Discussionmentioning
confidence: 99%
“…This aspect is of interest during ECP treatment because the risks of adverse reactions related to the infusion of granulocytes are minimized . RBC contamination of the product is also significant because it impairs the efficacy of UV‐A irradiation . Median Hct detected in our collections was satisfying, demonstrating the good property of the new software.…”
Section: Discussionmentioning
confidence: 78%
“…An ideal MNCs collection for ECP should contain a very low number of platelets (PLTs), granulocytes and red blood cells (RBC). In fact, contaminating cells may be responsible both for side‐effects during MNCs reinfusion to the patient and for impairing the efficacy of irradiation when the haematocrit is too high . A high‐quality MNCs collection is also important for novel cell therapy protocols .…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, efforts have been made to optimize the ECP procedure by evaluating the use of alternative photosensitizers 17,18 or modifying other parameters, such as 8-MOP incubation time, cell density, and hematocrit. 19,20 Whether ECP can be performed in the absence of a photosensitizer with only the UVA light irradiation regime has never been evaluated. The addition of 8-MOP to the apheresis product is handled differently by European compared to non-European authorities, where it is subject to a number of regulatory rules.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 In addition, the influence of parameters such as hematocrit, cell density, or 8-MOP incubation time on the efficacy of ECP has been addressed in vitro. 19,20 Here, we investigated whether the standard ECP procedure, based on the combined treatment of white blood cells (WBCs) with a photosensitizer and UVA light, could be simplified by exposing the cells to UVA light only. We therefore compared the efficacy of the gold standard of ECP treatment to that consisting only of various doses of UVA light and irradiation intervals in an in vitro model system by assessing the induction of apoptosis in different cell populations over time and the capacity of monocytes to respond to stimulation and to induce allogeneic T-cell proliferation.…”
Section: Introductionmentioning
confidence: 99%